Designing a touchless physical examination for a virtual Objective Structured Clinical Examination - Karkache, Wassim; Halman, Samantha; Tran, Christopher; Nie, Rui; Pugh, Debra (Canadian Medical Education Journal, 2024)
Purpose: Given the COVID-19 pandemic, many Objective Structured Clinical Examinations (OSCEs) have been adapted to virtual formats without addressing whether physical examination maneuvers can or should be assessed virtually. In response, we developed a novel touchless physical examination station for a virtual OSCE and gathered validity evidence for its use. Methods: A touchless physical examination OSCE station was pilot-tested in a virtual OSCE in which Internal Medicine residents were asked to verbalize their approach to the physical examination, interpret images and videos of findings provided upon request, and make a diagnosis. Differences in performance by training year were explored using ANOVA. In addition, data were analyzed based on a modified approach of Bloom's taxonomy of learning: knowledge, understanding, and synthesis. Results: Sixty-seven residents (PGY1-3) participated in the OSCE. Scores on the pilot station were significantly different between training levels (F=3.936, p=0.024, ηp2=0.11). The pilot station-total correlation (STC) was 0.558, and the item-station correlations (ITC) ranged from 0.115 to 0.571, with the most discriminating items being those that assessed higher orders of learning (understanding and synthesis). Conclusion: This touchless physical examination station was feasible, had acceptable psychometric characteristics, and discriminated between residents at different levels of training.